The Consumptive Significance of Images and Interface Values in Cyberpunk Cities - Mohseni, Hossein; Soheil, Kian (Text Matters: A Journal of Literature, Theory and Culture, 2020)
Cyberpunk is one of the latest genres in the development of science fiction. The genre emerged during the 80s and 90s, and in it the characters are confronted by an abundance of images and interface values. As a result, these images and values have become key identifying motifs of this genre. Referring to the theoretical conceptualizations of Adam Roberts about novum, and Lieven De Cauter on capsules and capsulization, the present study argues that the reason for the abundance of images and interface values is due to their facilitation of the consumption of novelties in cyberpunk cities. Within a scientific and rational discourse, images and interface values combine familiar and unfamiliar concepts and package them both as convenient commodities to be consumed by the characters of cyberpunk fiction. One of the key outcomes of such a combination, the study argues, is that the characters of cyberpunk fiction rely on the consumption of images and interface values as a convenient means to handle the overwhelming presence of technological and cybernetic advancements in the represented cities. This outcome turns the need to see and consume the cyberpunk world through images and interface values into an ideological necessity—or what can also be called a defense mechanism—for the characters against the technological shock of cybernetic advancements; a necessity whose qualities will be discussed in the study, as well.